The Role of Prices on Excludable Public Goods - Sören Blomquist; Vidar Christiansen (Center for Economic Studies and ifo Institute (CESifo), 2001)
When a poublic good ist excludable it is possible to charge individuals for using the good. We study the role of prices onexcludable public goods using an extension of the Stiglitz-Sternversion of the Mirrlees optimal income tax model. Our discussionincludes both the case where the public good is a final consumergood and the case where it is an intermediate good.We demonstrate that for a public consumer good charging apositive price may be desirable, but only under certain conditions.However, charging a lower than optimal price may be less efficientthan setting a zero price. Conditions are identified under which consumers should be rationed in their demand rather thanadjusting demand to price. We also conclude that producers using an intermediate public good as input should not be charged a positive price.
Keywords: 330; excludable public goods; public sector pricing; information constrained Pareto efficiency